Respiratory support of adults in the emergency department: A protocol for a prospective, observational, multicenter point prevalence study - O'Donnell J; Pirret A; Hoare K; McDonald E (Health Science Reports published by Wiley Periodicals LLC, 2023)
Background and Aims Providing respiratory support (RS) to patients may improve their oxygenation and ventilation, reducing the work of breathing. Emergency department (ED) patients often need RS; COVID-19 has heightened this need. Patients receiving RS may need escalation of their treatment; hence, studies considering the prevalence of escalation are warranted. Method This is a protocol for a prospective, observational, multicenter point prevalence study (PPS). Researchers will collect data over 2 days. All participants are adult ED patients needing RS. The setting is four EDs in New Zealand. The primary research question asks, “Which patients receiving RS require escalation of therapy in the ED?” For example, transitioning from conventional oxygen therapy (COT) to intubation is deemed an escalation of therapy. A sample size of 80 participants is required to resolve the primary research question. Secondary research questions: (1) Which patients receive nasal high flow (NHF) in the ED? (2) How is NHF therapy delivered in the ED? (3) What are the effects of NHF therapy on physiological and patient-centered outcomes? Research Electronic Data Capture (REDCap) will be used for data organization. Data will be imported for analysis from REDCap to IBM SPSS software (Statistics for Windows, Version 27.0). Data reporting on the primary outcome shall be considered by analysis of variance, regression modeling, and determination of two treatment effects: Odds Ratio and Number Needed to Treat. Statistical significance for inferential statistics shall use a two-sided α with p-values fixed at ≤0.05 level of significance and 95% confidence intervals. This protocol has ethical approval from Massey University, New Zealand. Conclusion This novel PPS may reduce the evidence and clinical practice gap on RS delivery and ED patient outcomes, as evidenced by the emergence of COVID-19.
© 2022 The Authors.
Keywords: COVID 19; emergency; nasal high flow; point prevalence; respiratory support